Innate Immunity Induced by the Major Allergen Alt a 1 From the Fungus Alternaria Is Dependent Upon Toll-Like Receptors 2/4 in Human Lung Epithelial Cells - Hayes, Tristan; Rumore, Amanda; Howard, Brad; He, Xin; Luo, Mengyao; Wuenschmann, Sabina; Chapman, Martin; Kale, Shiv; Li, Liwu; Kita, Hirohito; Lawrence, Christopher B. (Frontiers in Immunology, 2018)
Allergens are molecules that elicit a hypersensitive inflammatory response in sensitized individuals and are derived from a variety of sources. Alt a 1 is the most clinically important secreted allergen of the ubiquitous fungus, Alternaria. It has been shown to be a major allergen causing IgE-mediated allergic response in the vast majority of Alternaria-sensitized individuals. However, no studies have been conducted in regards to the innate immune eliciting activities of this clinically relevant protein. In this study, recombinant Alt a 1 was produced, purified, labeled, and incubated with BEAS-2B, A549, NHBE, and DHBE human lung epithelial cells. Alt a 1 elicited strong induction of IL-8, MCP-1, and Gro a/b/g. Using gene-specific siRNAs, blocking antibodies, and chemical inhibitors such as LPS-RS, it was determined that Alt a 1-induced immune responses were dependent upon TLRs 2 and 4, and the adaptor proteins MYD88 and TIRAP. Studies utilizing human embryonic kidney (HEK) cells engineered to express single receptors on the cell surface such as Toll-like receptors (TLRs), further confirmed that Alt a 1-induced innate immunity is dependent upon TLR4 and to a lesser extent TLR2.